1992
DOI: 10.1021/jo00038a030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of enantiomerically pure protected 4-oxo .alpha.-amino acids and 3-aryl .alpha.-amino acids from serine

Abstract: The organozinc reagent 13, prepared from the protected ¡9-iodo alanine derivative 3c using ultrasonic activation, is efficiently acylated using acid chlorides in the presence of bis(triphenylphosphine)palladium dichloride to give enantiomerically pure protected 4-oxo-a-amino acids 17 in 39-90% yield (13 examples). Zinc reagent 13 can also be coupled with aryl iodides in the presence of bis(tri-o-tolylphosphine)palladium dichloride to give enantiomerically pure protected phenylalanine analogues 26,29, and 30 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(60 citation statements)
references
References 1 publication
0
60
0
Order By: Relevance
“…Early work by Knochel and co-workers demonstrated that alkyl zinc reagents prepared by the reaction of zinc dust with an appropriate organohalide were not destroyed in the presence of acidic protons (pK a [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. [157,158] In 2006, Uchiyama et al reported that the halogen-metal exchange of a haloarenes bearing acidic hydrogen atoms could be accomplished with tBu 4 ZnLi 2 without quenching the reagent or the resulting aryl zincate. [159] For example, treatment of p-iodobenzylalcohol (192) with tBu 4 ZnLi 2 generated 193, which could be trapped with a variety of electrophiles in moderate to high yields (Scheme 80).…”
Section: Selecting Between Carbon-carbon Coupling Reactionsmentioning
confidence: 99%
“…Early work by Knochel and co-workers demonstrated that alkyl zinc reagents prepared by the reaction of zinc dust with an appropriate organohalide were not destroyed in the presence of acidic protons (pK a [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. [157,158] In 2006, Uchiyama et al reported that the halogen-metal exchange of a haloarenes bearing acidic hydrogen atoms could be accomplished with tBu 4 ZnLi 2 without quenching the reagent or the resulting aryl zincate. [159] For example, treatment of p-iodobenzylalcohol (192) with tBu 4 ZnLi 2 generated 193, which could be trapped with a variety of electrophiles in moderate to high yields (Scheme 80).…”
Section: Selecting Between Carbon-carbon Coupling Reactionsmentioning
confidence: 99%
“…In contrast to these aromatic amino acids bearing (pseudo)halogenated moieties, amino acid-based alkyl halides are not used directly as substrates in the Suzuki-Miyaura reaction. To date, their use is limited to the Negishi reaction of β-iodoalanine, β-iodohomoalanine, and iodobishomoalanine with various aryl iodides, to gain access to non-proteinogenic phenylalanine analogues [66][67][68][69]. For peptides that are prepared by chemical methods, SPPS easily enables the replacement of an aromatic amino acid with a non-natural (pseudo)halogenated analogue.…”
Section: Access To and Derivatization Of (Pseudo)halogenated Aromaticmentioning
confidence: 99%
“…This compound, which is easily derived from l-serine in a four-step sequence, [26] was treated with the enamine 12 derived from cyclohexanone and pyrrolidine to give 14. Removal of the N-Boc protecting group provided an amino ester, which cyclized to 15 upon heating under acidic conditions.…”
Section: Dubuffet and Langlois Reportedmentioning
confidence: 99%